Structural Study of the Compound [(C10O8H2)2 (C4N2H6)].2H2O Synthesized by Hydrothermal Condition - Halouani, Manel; Abdelhedi, M.; Dammak, M.; Audebrand, N.; Ktari, L. (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
A new metal–organic compound [(C10O8H2)2(C4N2H6)].2H2O(I) was hydrothermally synthesized from an aqueous solution of Fe (NO3)3 9H2O, (btec) (btec= 1, 2, 4, 5-benzenetetracarboxylic acid) and piperazine. Compound I crystallizes in the triclinic system with the P1 space group. The unit cell parameters are a = 8.271 Å, b = 8.500 Å, c = 9.660 Å, α = 87.12°, β = 89.53°, γ = 70.91°, Z= 2, V= 640.96(6) Å3 and Dx= 1.602g/cm3. The refinement converged into R= 0.047 and RW = 0.059. The structure, determined by single crystal X-ray diffraction, consists of two carboxyl group, piperazine and two molecules of water.